The Influence of Managerial Ownership, Profitability, Leverage, Company Size, and Capital Structure on Dividend Policy in Oil and Gas Sub-Sector Companies Listed on the Indonesia Stock Exchange for the Period 2019–2023 from an Investment Literacy Perspective - Alifiya Agustira; Lovelly Dwinda Dahen; Syailendra Eka Saputra (Global Action and Education for Society, 2026)
This study aims to analyze the effect of Managerial Ownership, Profitability, Leverage, Firm Size, and Capital Structure on Dividend Policy in manufacturing companies within the Oil and Gas sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. This research is associative in nature, which means it seeks to determine the relationship or influence between two or more variables. Since it focuses on analyzing the influence of independent variables—Managerial Ownership, Profitability, Leverage, Firm Size, and Capital Structure—on the dependent variable, Dividend Policy, in oil and gas manufacturing companies listed on the IDX, the study falls into the category of associative research. The results of the study indicate the following: First, the managerial ownership variable (X1) has a regression coefficient of -0.058367 with a t-statistic value of -0.327488 < t-table of 1.795, and a significance value of 0.019 < 0.05. Based on these results, the decision taken is to accept H0 and reject Ha.Second, the leverage variable (X2) has a regression coefficient of -0.023137 with a t-statistic value of -0.152861 > t-table of 1.795, and a significance value of 0.442 < 0.05. Based on these results, the decision is to reject H0 and accept Ha. Third, the firm size variable (X3) shows a regression coefficient of 0.149941 with a t-statistic value of 0.772473 > t-table of 1.943, and a significance value of 0.442 < 0.05. Thus, the decision taken is to reject H0 and accept Ha. Fourth, the capital structure variable (X4) has a regression coefficient of 0.641098 with a t-statistic value of 1.284546 > t-table of 1.795, and a significance value of 0.203 < 0.05. Therefore, the decision taken is to accept H0 and reject Ha. Fifth, based on the simultaneous hypothesis testing of the variables Managerial Ownership, Profitability, Leverage, Firm Size, and Capital Structure, the F-statistic value is 1.1814 > F-table of 2.203, with a probability value (F-statistic) of 0.036 < 0.05. Thus, the decision taken is to reject H0 and accept Ha.